(untitled) (Bangladesh Pharmaceutical Journal, 2018)
The methanol extract of aerial parts of Dioscorea alata and its organic and aqueous soluble materials were subjected to screenings for antioxidant, cytotoxic, thrombolytic, membrane stabilizing and antimicrobial activities. The polyphenol content and DPPH free radical scavenging assay were conducted to evaluate the antioxidant activity. The total phenolic content was found to vary for different test samples ranging from 23.69 ± 0.25 to 26.60 ± 0.22 mg of GAE/gm of dried extract. In DPPH method the chloroform soluble fraction (CSF) of D. alata revealed the highest free radical scavenging activity with IC5025.33 ± 0.05 μg/ml. The petroleum ether soluble fraction (PESF) exhibited highest cytotoxic potential having LC50 value of 6.1 μg/ml. During the membrane stabilizing assay, the aqueous soluble fraction (AQSF) inhibited 31.91% and 47.55% haemolysis of RBC in hypotonic solution- and heat-induced method, respectively. In thrombolytic assay, the chloroform soluble fraction (CSF) displayed 40.45% clot lysis. On the other hand the carbon tetrachloride (CTCSF) and chloroform soluble fraction (CSF) revealed mild to moderate antimicrobial activity with zone of inhibition ranging from 8 to 12 mm. Bangladesh Pharmaceutical Journal 20(2): 200-204, 2017